(3GdLGeY GdcGaj aj abg GdRjOjIs - (3CHh YHO Gddg eMeO Hf Ydj Hf GdMSf YHO GdQMef Gdchaj GdMSfjs
(3ChdgG (B:s
(3Chdg HYO GdHSedI (B: (3bGd eMeO hEPG QaY QLd QLdkG Ydi KhH aGfMQb GdKhH VefI GdOGaY s
(3BNQgG (B:s
(3BNQg HYfhGf (B( (3ai EJHGY GdSfI ai GdLgGO (B) (3bhdg hbGd Ydi aEf HOChG aGHJOhG , hEf ESJfUQhce aGfUQhge , hdG JUQYce GdHdjI Je GdcJGH s
(3GdLRAGf (B5s
6 (3ef GdfSNI GdSGHbI cJHJ GdYfhGfGJ HNW eLhO hjfJgi GdLRA GdNGeS efgG YfO GdhQbI (B149 (3Cs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda SfI (B973s
Keywords: (3abg GdePGgH GdCNQis